Role of awake thoracoscopy in diagnosis before chest tube insertion in lung empyema: A Case Report - Kartika, Ronald Winardi; Hasan, Afrizal; Dwiyanti, Hapsari; Yoshua, Edwin; Gisela, Esther; Supriyanto, Jaya (Journal of Indonesia Vascular Access, 2025)
Background: Awake thoracoscopy diagnostic (ATD) is a valuable procedure performed before the insertion of a chest tube to visually identify lung and pleural diseases. This technique, which utilises thoracic spinal anaesthesia, allows patients to remain conscious during the procedure and eliminates the need for intensive care unit (ICU) admission post-operation. The purpose of this study is to demonstrate ATD's effectiveness in early identification and management of complex pleural infections, particularly in high-risk and resource-constrained settings Case Report: This case report describes a 56-year-old male who presented to the Emergency Department of RSUP Sitanala Tangerang with worsening intermittent dyspnea over three days, accompanied by low-grade fever, decreased appetite, weight loss, and a persistent cough. Diagnostic imaging revealed significant loculated pleural effusion, and thoracentesis yielded only 10 cc of purulent fluid, indicating a possible infectious process. A thoracic surgeon recommended awake thoracoscopy under thoracic spinal anaesthesia for direct evaluation and management. Intraoperative findings included thick pleural peel, necessitating thorough irrigation of the pleural cavity. A water-seal drainage (WSD) system was established for ongoing fluid management. Conclusion: Awake thoracoscopy diagnostic demonstrates significant advantages in the preoperative evaluation of patients with pleural diseases, particularly in cases involving active tuberculosis. Its minimally invasive nature and the benefits of awake procedures underscore its potential as a preferred diagnostic approach in thoracic surgery.